ANALISIS KUALITAS FISIKA PERAIRAN BERDASARKAN NILAI PADATAN TERSUSPENSI DAN KEKERUHAN PERAIRAN DI BENDUNGAN TELAGA TUNJUNG DESA TIMPAG, KECAMATAN KERAMBITAN, KABUPATEN TABANAN – BALI - Dewa Gde Tri Bodhi Saputra; I Wayan Arthana; Made Ayu Pratiwi (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2016)
Telaga Tunjung reservoir has a function for irrigation for around 1.335 Ha irrigation land. Beside, also for supplying clean water to the household in 6 village in Selemadeg District, 2 village in Kerambitan District and 1 village in Tabanan District. The clean water also used in Soka tourism area and in Berembeng village. Telaga Tunjung reservoir also used for water resources conservation. This research aim to know total suspended solid at Telaga Tunjung reservoir as a reference for reservoir management. The method of this research were survey method and laboratory analyzing. The results of TSS in Telaga Tunjung reservoir were 2.667-91.278 mg/L. The lowest value of TSS was in January and the highest in February. The condition of TSS was in January (no rain). The difference between inlet and outlet was 19.051 mg/L or 61,22 %. In the downstream of reservoir, the TSS was getting lower. In February the differences between inlet and outlet was 53.315 mg/L or 140,43 %. The TSS at inlet, upstream and outlet in February increased significantly compared that in January and March. In February there was some location that exceed the second class water standard of central Government Regulation Number 82 in 2001 and Bali’s Governor Regulation number 8 in 2007.